PENGARUH PENGGUNAAN MEDIA POWTOON TERHADAP MINAT BELAJAR SISWA SMAN 12 BULUKUMBA - Supri, Misra Ulfaina; Nurindah; Nawir, Muhammad (Jurnal Pendidikan dan Pembelajaran, 2023)
This study aims to determine the effect of using Powtoon media on students' interest in learning at SMAN 12 Bulukumba. This type of research is quantitative or experimental research (Pre Experiment) with a One-Shot Case Study design. The population in this study were all students of SMAN 12 Bulukumba with a total of 397 people. The sample in this study were students of class XI MIPA 1 with a total of 27 students, who were selected through purposive sampling. Data collection techniques in this study were observation, tests, and documentation. The results of the study found that the count was 0.390 so it was categorized as having a low correlation level, which was in the range of 0.21-0.40. This value also shows that there is a positive relationship between the use of Powtoon media and students' interest in learning because the value of the correlation coefficient is positive. Based on the results of this study, it can be concluded that there is an effect of using Powtoon media on the learning interest of SMAN 12 Bulukumba students.